Inhalation of Pelargonium graveolens Essential Oil Alleviates Pain and Related Anxiety and Stress in Patients with Lumbar Spinal Stenosis and Moderate to Severe Pain - Eunhye Seo; Yoonah Cho; Jeong-Min Lee; Geun Hee Seol (MDPI AG, 2023)
Pain in lumbar spinal stenosis (LSS) patients is closely associated with psychological factors, including anxiety, stress, and depression, and is a critical determinant of patient daily functionality and overall quality of life. The present study evaluated the effects of inhalation of Pelargonium graveolens (geranium) essential oil (GEO) on pain and related psychological factors in LSS patients. Fifty-nine patients, categorized as having mild or moderate to severe pain based on pain visual analog scale (VAS) scores, were randomly assigned to inhalation of 1% GEO or placebo control (PC). No significant differences between GEO and PC were observed in patients with mild pain, whereas differences in anxiety-VAS and stress-VAS scores were observed in patients with moderate to severe pain. Anxiety-VAS and stress-VAS scores decreased significantly after GEO but not after PC inhalation. Regardless of the severity of pain, post-intervention pain-VAS scores were significantly lower in the GEO group than in the PC group. In summary, GEO reduced pain and improved anxiety and stress, particularly among patients with moderate to severe pain. These findings suggest that GEO inhalation may have potential as an adjunct therapy for improving pain management and alleviating anxiety and stress in LSS patients with insufficient responses to pharmacological pain control.